Improving E-commerce Experience with Django Framework - Jokonowo, Bambang; Mubarak, Roy; Cherid, Annis; Rivai, Adriean Baihaqi; Ahmad, Rijalul Awal (Journal Collabits, 2024)
The Rise of Django Framework in Ecommerce Development: A Comprehensive Guide The advent of the digital era has triggered an unprecedented surge in e-commerce platforms, necessitating robust frameworks for their development. In this landscape, Django emerges as a key player, offering a comprehensive solution for building scalable and efficient online shopping environments. This paper delves into the utilization of Django Framework in creating e-commerce platforms that align with the evolving needs of modern businesses and consumers. Adopting a practical approach, we explore how Django integrates with core e-commerce functionalities such as inventory management, payment processing, and user analytics. We emphasize the importance of seamlessly blending Django's advanced features with e-commerce tools to ensure a smooth and efficient shopping experience. We showcase the success of our approach in crafting an e-commerce website that is efficient, reliable, and adaptable to the dynamic shifts of the business landscape. Our findings highlight the pivotal role of Django Framework in providing a sturdy foundation for developing successful and responsive e-commerce platforms in the rapidly evolving digital era. Through a combination of theoretical insights and practical applications, this paper provides valuable insights for developers and businesses alike who seek to optimally leverage Django Framework in optimizing e-commerce business success. In essence, our research confirms the enduring relevance and effectiveness of Django in driving efficiency and innovation within the realm of online commerce.